UPAYA MENINGKATKAN BERPIKIR KRITIS PESERTA DIDIK MELALUI MODEL PEMBELAJARAN ONLINE MINI-DEBATE COMPETITION PADA MATA PELAJARAN PRAKARYA DAN KEWIRAUSAHAAN DI KELAS XI IPS SMA LABSCHOOL CIRENDEU - Nurkholik, Adam (CV Sintesia, 2024)
The Development of student’s critical thinking ability is crucial because based on the survey released by PISA (2018) found that the quality of Indonesian student’s critical thinking are in rank of 72 of 78 countries. One of the active learning model to develop the critical thinking is through Online Mini-Debate Competition. This study was conducted in two cycles by using action research consists of four phases: Plan, Action, Observation, and Reflection. Based on the observation data, found that the three indicators of success in implementing the Mini-Debate Competition Online learning model and eleven indicators of critical thinking with the criteria of value A (very good) respectively. It can be concluded based on the results of the debate that the online learning process has been successful and the critical thinking skills of 34 students have improved on XI IPS 2 in SMA Labschool Cirendeu with subjects of Craft and Entrepreneurship (PKWU).